Assessing the Reliability and Transparency of ScholarGPS: A Website Review - M, Chaman Sab; KK, Mueen Ahmed; Yunus, Mohammed (Journal of Data Science, Informetrics, and Citation Studies, 2026)
The rapid expansion of scholarly content and digital research tools has led to an increasing dependence on bibliometric indicators and academic ranking systems. ScholarGPS, an emerging research analytics platform, claims to offer comprehensive rankings of scholars, institutions, and disciplines using proprietary algorithms and large-scale publication data. This article critically examines the reliability and transparency of ScholarGPS through a systematic website review enriched by a literature-based analysis of bibliometrics, ranking methodologies, and data governance. The review focuses on the platform’s data sources, methodological clarity, algorithmic design, fractional authorship logic, and the degree of openness in its reporting. Findings indicate that while ScholarGPS offers broad coverage and uses modern scientometric constructs such as fractional h-index and self-citation normalisation, there are notable gaps in metadata disclosure, algorithmic weight specifications, and governance transparency. The article concludes with implications for researchers, institutions, and evaluators, offering recommendations for responsible use and future methodological improvements
Keywords: Academic Ranking; H-index; Scopus; ScholarGPS; Web of Science; Website review